THE PLACELESS CHAPEL: MEMORY, MEANING AND DESTRUCTION IN SACRED SPACE = KAPELA BREZ KRAJA : SPOMIN, POMEN IN UNIČENJE V SVETEM PROSTORU - Eisch-Angus, Katharina (Traditiones, 2018)
An ethnographic narrative from Israel, with its sacred sites marked by war and destruction, explores the dynamics of absence and presence, of imagination and reality of religious dwelling places. This idea of a chapel of placelessness underlies an ethnographic field diary written in the summer 2015 in Israel. Sacred spaces offer their presence built on absence, on layers of cultural memory. The focal point of my diary is the town and the sacred sites of Nazareth, built on the incarnation of the word, and, more concretely, on Mary’s house. It is an everyday dwelling place in local narratives, and a centre point of worldwide pilgrimage. Yet, at the same time, the House of Mary is itself imagined as a travelling chapel, absent, but ubiquitously present in innumerable Loreto churches.